The Preventing of Religious Extremism in Islamic Religious Universities through Fiqh Wasatiyah Approach - Akhmad Muhaini; Suwito Suwito; Khusnul Khotimah; Muhajir Muhajir; Koteit Naim (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Abstract: This study aims to determine student responses to religious extremism and find out how to prevent the spread of religious extremism to students at Islamic religious colleges through the wasatiyah fiqh approach. This type of Research is Fields research, which uses interview and documentation data collection techniques. In selecting informants, the researcher used the Purposive Sampling method. The data analysis technique used was qualitative analysis. After conducting an in-depth study of religious Extremism at Islamic religious universities, several conclusions were found: first, students were divided into several groups in response to religious extremism, namely groups that rejected religious extremism, groups that accepted religious extremism, and groups that did not care about religious extremism. The second conclusion, several things can be done so that the understanding of extremism does not develop in Islamic religious colleges, namely by conducting Socialization of wasatiyah fiqh and the dangers of religious extremism, strengthening Islamic teachings (fiqh) wasatiyah by practicing Islamic teachings that are balanced between text and context. Next, to produce humanist Islamic teachings, love peace, and prioritize tolerance and religious harmony. The following method is to cooperate with Islamic organizations with the wasatiyah line of fiqh and give firm punishment to students who understand religious extremism and do not understand wasatiyah fiqh. Keywords: (Fiqh Wasatiyah, Understanding of Religious Extremism, Islamic religious Universities Abstrak: Penelitian ini bertujuan untuk menentukan respons mahasiswa terhadap ekstremisme agama dan mencari cara mencegah penyebaran ekstremisme agama kepada mahasiswa di perguruan tinggi agama Islam melalui pendekatan fiqh wasatiyah. Jenis penelitian ini adalah penelitian lapangan, yang menggunakan teknik pengumpulan data wawancara dan dokumentasi. Dalam memilih informan, peneliti menggunakan metode Purposive Sampling. Teknik analisis data yang digunakan adalah analisis kualitatif. Setelah melakukan studi mendalam tentang Ekstremisme Agama di perguruan tinggi agama Islam, ditemukan beberapa kesimpulan: pertama, mahasiswa terbagi menjadi beberapa kelompok dalam merespons ekstremisme agama, yaitu kelompok yang menolak ekstremisme agama, kelompok yang menerima ekstremisme agama, dan kelompok yang tidak peduli terhadap ekstremisme agama. Kesimpulan kedua, beberapa hal dapat dilakukan agar pemahaman tentang ekstremisme tidak berkembang di perguruan tinggi agama Islam, yaitu dengan melakukan sosialisasi tentang fiqh wasatiyah dan bahaya ekstremisme agama, memperkuat pengajaran Islam (fiqh) wasatiyah dengan mengamalkan ajaran Islam yang seimbang antara teks dan konteks. Selanjutnya, menghasilkan ajaran Islam yang humanis, mencintai perdamaian, dan mengutamakan toleransi dan harmoni agama. Metode berikutnya adalah bekerjasama dengan organisasi Islam yang mengikuti garis fiqh wasatiyah dan memberikan hukuman tegas kepada mahasiswa yang memahami ekstremisme agama dan tidak memahami fiqh wasatiyah.Kata kunci: Fiqh Wasatiyah, Pemahaman Ekstremisme Agama, Perguruan Tinggi Agama Islam